A Phase III Study Evaluating Continuation, Tapering, and Withdrawal of Certolizumab Pegol After One Year of Therapy in Patients With Early Rheumatoid Arthritis. Issue 10 (12th September 2017) - Weinblatt, Michael E.; Bingham, Clifton O.; Burmester, Gerd‐Rüdiger; Bykerk, Vivian P.; Furst, Daniel E.; Mariette, Xavier; van der Heijde, Désirée; van Vollenhoven, Ronald; VanLunen, Brenda; Ecoffet, Cécile; Cioffi, Christopher; Emery, Paul
Abstract : Objective: In disease‐modifying antirheumatic drug–naive patients with early rheumatoid arthritis (RA) who had achieved sustained low disease activity (a Disease Activity Score in 28 joints using the erythrocyte sedimentation rate of ≤3.2 at both week 40 and week 52) after 1 year of treatment with certolizumab pegol (CZP) at a standard dose (200 mg every 2 weeks plus optimized methotrexate [MTX]), we evaluated whether continuation of CZP treatment at a standard dose or at a reduced frequency (200 mg every 4 weeks plus MTX) was superior to stopping CZP (placebo plus MTX) in maintaining low disease activity for 1 additional year. Methods: A total of 293 patients from period 1 of our study were re‐randomized 2:3:2 in period 2 to CZP at a standard dose (n = 84), CZP at a reduced frequency (n = 127), or placebo plus MTX (CZP stopped) (n = 82). The primary end point was the percentage of patients who maintained low disease activity throughout weeks 52–104 without flares. We used a hierarchical testing scheme, comparing CZP at a standard dose with CZP stopped. If P < 0.05 was achieved, then CZP at a reduced frequency was compared with CZP stopped (nonresponder imputation). Results: The 293 patients from period 1 represented 36% fewer patients than projected, yielding a smaller number of patients eligible for period 2. Higher proportions of patients treated with the standard and reduced frequency regimens maintained low disease activity than those who had stopped CZP (48.8% and 53.2%, respectively, versus 39.2% [ P = 0.112 and P = 0.041, respectively; nominal P value, first hierarchical test not significant]). Similar trends were observed for radiographic nonprogression (change from baseline of ≤0.5 in modified Sharp/van der Heijde score; 79.2% and 77.9% of patients, respectively, versus 70.3%) and normative physical function (Health Assessment Questionnaire disability index score of ≤0.5; 71.4% and 70.6% of patients, respectively, versus 57.0%). Safety profiles were similar between all groups, with no new safety signals identified for continuing CZP to week 104. No deaths were reported. Conclusion: The study failed to meet its primary end point. However, there were no clinically meaningful differences between the standard and reduced frequency doses of CZP plus MTX; both controlled RA more effectively than stopping CZP.